Change the world without taking power : the meaning of revolution today - Holloway, John, 1947- (Pluto Press, 2019)
This book is a profound search for a theory of social change. Through clearing away the cobwebs of revolutionary socialism, it renews the fight for the ending of capitalism and the construction of a world based on the mutual recognition of human dignity. After a century of failed attempts by radical projects, the concept of revolution itself is in crisis. By asking the deepest questions about the nature of humanity, work, capitalism, organization and resistance, the author looks carefully at modern protest movements and provides tools for creating new strategies. First published in 2002, this book marked a shift in the understanding of Autonomism, Anarchism and Marxism, and helped form the perspectives of a new generation who are today changing the world.